Facile fabrication and optimization of bowl-like ZnO/CdS nano-composite thin films with hierarchical nanopores and nano-cracks for high-performance photoelectrochemistry. (6th December 2018) - Lai, Yan; Chi, Liping; Liu, Bingwu; Li, Zelin
Abstract: A special nano-structured composite ZnO/CdS thin film with hierarchical nanopores and nano-cracks has been synthesized by a facile two-step method for the first time, in which both loadings of ZnO and CdS are optimized. We first fabricated the hierarchical nanoporous ZnO thin film through rapid gas/liquid interface assembly and layer-by-layer transfers of bowl-like ZnO nanoparticles for thirteen times. The ZnO nanobowls are prepared by a simple solution chemical reaction without using any templates. After annealing, the assembled ZnO film is sensitized with CdS nanoparticles by successive ionic layer adsorption and reactions for six cycles. Nano-cracks form for the ZnO/CdS nano-composite film by calcination, which is due to the different thermal expansion behavior between the ZnO film and the CdS layer. The facilely optimized ZnO/CdS films can serve as a promising photoanode in a photoelectrochemical cell, and it can generate a saturated photocurrent density as high as 7.8 mA cm −2  at −0.9 V (vs. Hg|Hg2 SO4 |saturated K2 SO4 ) under visible light illumination of 100 mW cm −2 in an aqueous solution of 0.5 M Na2 S, corresponding to a solar-to-electricity conversion efficiency of 6.6%. Graphical abstract: Highlights: Bowl-like ZnO nanoparticles are prepared by sol aging in a weak alkaline solution. The ZnO nanoparticles are assembled into a thin layer at the gas/liquid interface. Hierarchical nanoporous ZnO films form by loading thirteen layers of ZnO on FTO. Calcination of CdS modified ZnO films generates nano-cracks enhancing mass transfer. The ZnO/CdS photoanode shows a high photocurrent density at a low applied potential.